Study on effect of peptide-conjugated near-infrared fluorescent quantum dots on the clone formation, proliferation, apoptosis, and tumorigenicity ability of human buccal squamous cell carcinoma cell line BcaCD885 - Deping Sun (Dove Medical Press, 2010)
Deping Sun1, Kai Yang1, Gang Zheng2, Zhigang Li1, Yuan Cao11Department of Oral and Maxillofacial Surgery, the First Affiliated Hospital, Chongqing Medical University, Chongqing, China; 2Chongqing Hospital of Traditional Chinese Medicine, Chongqing, ChinaAbstract: Quantum dots (QDs) have shown great development potential in noninvasive imaging and monitoring of cancer cells in vivo because of their unique optical properties. However, the key issue of whether or not QDs-labeled cancer cells affect the proliferation, apoptosis and in vivo tumorigenicity ability has not been reported. The primary issue is if the results obtained from the noninvasive visualization of QDs-labeled tumors are scientific. Here, we applied peptide-linked near-conjugated fluorescent QDs to label human buccal squamous cell carcinoma cell line (BcaCD885). We performed in vivo tumorigenicity ability assays, tumorigenic cells proliferation, and apoptotic capability assays detected by flow cytometry and plate clone formation experiment, and found that peptide-linked near-conjugated fluorescent QDs labeling did not affect the growth, proliferation, apoptosis, and tumorigenicity ability of those cancer cells. Our study provides scientific foundation to support the application of near-infrared fluorescent QDs in noninvasive imaging and monitoring of cancer cells in vivo.Keywords: quantum dots, near-infrared fluorescence, oral cancer, proliferation, apoptosis, tumorigenicity